Depressive symptoms are related with hemostatic factors in middle-aged women: A report from the Study of Women Health Across the Nation (SWAN) - Castilla, Ruby C; Bromberger, Joyce T; Zhang, Yangang; Perel, James M; Matthews, Karen A (MedUNAB, 2004)
Resumen Objetive: Depression may be a risk factor for coronary heart disease (CHD) morbidity and mortality, but the mechanims(s) for the association are not established. the present study examined the relationship between one possible mechanism, hemostatic factors, and depressive symptoms in middle-aged women. [Castlla RC, Bromberger JT, Zhang Y, Perel JM, Matthews KA. Depressive symptoms are related with hemostatic factors in middle-aged women: A report from the Study of Women Health Across the Nation (SWAN). MedUNAB 2004;7:57-64]. Key words: Hemostatic factors, depression, mid-life, women.